Gambaran Kemandirian Lansia dalam Melakukan Aktivitas Sehari Hari Berdasarkan Indeks Katz di Desa Sengka Kecamatan Bontonompo Selatan Kabupaten Gowa Tahun 2025 - Nurhikma Nurhikma; Sartika Sartika; Kasmawati Kasmawati; Didin Wahyudi (Prodi Keperawatan Universitas Syekh Yusuf Al Makassari Gowa, 2026)
And cognitive functions due to the aging process. This decline affects their independence in performing basic daily activities such as bathing, eating, and mobility. Maintaining independence is essential for ensuring the quality of life among the elderly, both in terms of physical health and psychosocial well-being. This study aims to describe the level of independence among the elderly in carrying out daily activities based on the Katz Index in Sengka Village, Bontonompo Selatan Sub-district, Gowa Regency, in the year 2025. The Katz Index is used to assess the elderly's ability to perform six basic activities of daily living: bathing, dressing, toileting, transferring, continence control, and eating. This study employed a descriptive quantitative design with a survey approach. The sample consisted of 30 elderly individuals who met the inclusion criteria, selected through accidental sampling. Data were collected through interviews using a standardized Katz Index questionnaire. The results showed that out of 30 respondents, 29 (96.7%) were categorized as independent, while only 1 respondent (3.3%) was found to be totally dependent. Factors influencing the level of independence included age, gender, and general health condition of the respondents. These findings indicate that the majority of elderly individuals in Sengka Village still possess a high level of independence. Therefore, this study is expected to serve as a basis for healthcare workers and local government in designing promotive and preventive programs aimed at maintaining and improving the quality of life of the elderly population.